Prayer Psychotherapy as an Implementation of the First Precepts of Pancasila - Alfiyah Makarrim (CV. Rayyan Dwi Bharata, 2022)
Psychotherapy is the main solution in curing mental health problems today. One of the simple things we do like praying is one of the psychotherapeutic practices. For in a state of prayer one will feel tranquility, peace, and even feel the presence of god. Along with that, in the first precept of pancasila, it is explained that god is one, the only creator of the universe, so that the activity of praying becomes a sign of trust and belief, as well as one's need for the existence of the one true god.